'Spaces of Exclusion' in community water governance: A Feminist Political Ecology of gender and participation in Malawi's Urban Water User Associations. Issue 95 (October 2018) - Adams, Ellis Adjei; Juran, Luke; Ajibade, Idowu
Highlights: Much of the literature on water and gender focuses on rural irrigation systems. We examine gender and water in urban water governance using Feminist Political Ecology. Socio-cultural practices, power relations and micro-politics undermined women's participation. Future work will explore women's pathways to leadership in urban water governance. Abstract: Much of the literature on gender dimensions of community-based water governance focuses on irrigation systems in rural areas. Largely overlooked is how gender dynamics influence participation in community-based urban water governance systems. To address this gap, we use insights from Feminist Political Ecology (FPE) to examine whether and how community-based governance of drinking water in an urban context leads to (in)equitable gender participation and decision making. Using household surveys (n = 415), key informant interviews (n = 19), focus-group discussions (n = 14), we explore gender dynamics and power relations underpinning participation, decision making processes, and employment and benefit sharing arrangements among Water User Associations (WUAs) in the urban informal settlements of Lilongwe, Malawi. We find that WUAs do not guarantee equitable gender participation. Rather, inequitable participation is simply reified through: (1) gendered representation in WUA structures; (2) socio-cultural practices and women's self-exclusion; and (3) community micro-politics and power relations. Our findings contradict the notion that community-based governance of water leads to equitable participation and empowerment of women. The policy implications are that without systematic efforts to incorporate women's needs, interests, and voices, so-called participatory approaches to water governance will only serve to suppress women's agency and reinforce existing gender-based inequalities. Future work will explore the pathways to women's leadership in the WUAs and interrogate how women on the board and executive committees navigate their way up the hierarchy, their experiences in a male-dominated water governance scheme and their recommendations for how WUAs can improve women's participation.